Risk aware Access Control model for Trust Based collaborative organizations in cloud - Aluvalu, Rajanikanth; Keerthi Chennam, Krishna; A.Jabbar, M.; Sarfaraz Ahamed, Shaik (International Journal of Engineering and Technology, 2018)
Secure interactions between collaborative organizations having their applications and data stored in â€œCloud Computingâ€ are a critical issue. Access control is the biggest challenge and trust is regarded as an essential secured relationship within a distributed system. Basic access control models, like Discretionary Access Control, Mandatory Access Control, and Role Based Access Control, cannot satisfy requirements in such environment, and need some improvements. During the collaboration, the attitude of the user may change. Therefore, in this context, adding trust management to an access control model is mandatory. To achieve this goal, in this paper, a new trust model to control access in the cloud is proposed. The aim is to monitor in real-time security for collaborative organizations, having decided to migrate to the cloud.Â Â